The influence of naturalistic, directionally non-specific motion on the spatial deployment of visual attention in right-hemispheric stroke. (November 2016) - Cazzoli, Dario; Hopfner, Simone; Preisig, Basil; Zito, Giuseppe; Vanbellingen, Tim; Jäger, Michael; Nef, Tobias; Mosimann, Urs; Bohlhalter, Stephan; Müri, René M.; Nyffeler, Thomas
Abstract: An impairment of the spatial deployment of visual attention during exploration of static (i.e., motionless) stimuli is a common finding after an acute, right-hemispheric stroke. However, less is known about how these deficits: (a) are modulated through naturalistic motion (i.e., without directional, specific spatial features); and, (b) evolve in the subacute/chronic post-stroke phase. In the present study, we investigated free visual exploration in three patient groups with subacute/chronic right-hemispheric stroke and in healthy subjects. The first group included patients with left visual neglect and a left visual field defect (VFD), the second patients with a left VFD but no neglect, and the third patients without neglect or VFD. Eye movements were measured in all participants while they freely explored a traffic scene without (static condition) and with (dynamic condition) naturalistic motion, i.e., cars moving from the right or left. In the static condition, all patient groups showed similar deployment of visual exploration (i.e., as measured by the cumulative fixation duration) as compared to healthy subjects, suggesting that recovery processes took place, with normal spatial allocation of attention. However, the more demanding dynamic condition with moving cars elicited different re-distribution patterns of visual attention, quite similar to those typically observed in acute stroke. Neglect patients with VFD showed a significant decrease of visual exploration in the contralesional space, whereas patients with VFD but no neglect showed a significant increase of visual exploration in the contralesional space. No differences, as compared to healthy subjects, were found in patients without neglect or VFD. These results suggest that naturalistic motion, without directional, specific spatial features, may critically influence the spatial distribution of visual attention in subacute/chronic stroke patients. Highlights: Naturalistic motion influences spatial attention in chronic stroke patients. The direction of this influence depends on the resulting syndrome. Patients with neglect and additional visual field defect show an ipsilesional bias. Patients with a visual field defect only show a contralesional bias.